New Locality Records of Hersilia orvakalensis Javed, Foord & Tampal, 2010 (Araneae: Hersiliidae) from Western India - Trivedi, Varsha M.; Dal, Parin I. (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.